Testing the Intensity of Macroeconomic Indicators and Institutional Quality on Deposit of Banks and Financial Institutions of Nepal - Bista, Smeeth; Bishwakarma, Sagar (Nepalese Journal of Statistics, 2025)
Background: Nepal's banking sector is currently experiencing an imbalance characterized by high deposit but low demand of credit reflected by contraction of aggregate demand. Issues related to institutional governance are no less. The volume, growth, and stability of these deposits are not only determined by the operational strategies of banks but are also influenced by a range of macroeconomic indicators and institutional quality. Objective: This situation prompted a study to examine the relationship between macroeconomic indicators, institutional quality and deposit of banks and financial institutions of Nepal. Materials and Methods: Analyzing 48 years of data from 1975 to 2023 sourced from various economic surveys, annual reports of Nepal Rastra Bank. At first, study used ARDL technique to explore the relationship of macroeconomic indicators with deposit of banks and financial institutions and then the relationship is explored with remittance and institutional factors. Robustness of these results are tested employing Granger Causality. Results: GDP revealed positive significant (0.195) effect on deposit growth. In the long run, lagged effect of money supply reduced (-0.604) deposit but it increased (1.189) deposit if lag is not considered. Effect of money supply in the short run was positively significant (1.189). Exchange rate depreciation was significant and contributed positively (0.046). Summation of recurrent and financial expenditure also indicated positive significant effects (0.029) on deposits. Capital expenditure exhibited positive significant effect in both long run and short run (0.004). Remittance demonstrated strong positive significant relation (0.247) and most of the institutional factors like political stability (0.005), rule of law (0.001), regulatory quality (0.006) and voice and accountability (0.002) contributed positively in deposit mobilization while government effectiveness contracted (-0.007) deposit, potentially representing structural inefficiencies in bank based financial system. Conclusion: This paper concludes that effective management of money supply, exchange rate stability together with fiscal discipline and enhancing the effectiveness of capital expenditure from the side of fiscal policy are crucial for promoting deposit mobilization. Furthermore harnessing the remittance into productive sectors, strengthening institutional qualities like rule of law and regulatory quality, political stability and government effectiveness are essential for ensuring efficient deposit mobilization and diversification.